Medicalized childhood: a study on the constitution of children with school complaints - Vieira de Souza, Simone (2022)
This work presents a clipping about the meanings produced by the child with school complaints, having as assumptions the Critical School Psychology. The study included five children/students aged between 12 and 13 years, referred for psychological care at the psychology service of a community university, as well as the families and teachers of these children. It is a qualitative research and the methodological process emphasizes the personal meaning that the children perceive, in the crossings marked by the school complaint. The focus of the investigation was, therefore, the child's point of view, with the mediations lived in the space of school and family being privileged. The study demonstrates that successive experiences of humiliation, exclusion and medicalization produce suffering, in addition to attributing meaning to stories of poor school success. On the other hand, it is evident that when children/students have experiences that validate their potency, there is a possibility of finding themselves strange in the usual place of being incapable and of imprinting new meanings on their history.